Surgical excision of ovarian endometriomas: Does it truly impair ovarian reserve? Long term anti‐Müllerian hormone (AMH) changes after surgery. Issue 11 (30th September 2015) - Vignali, Michele; Mabrouk, Mohamed; Ciocca, Erika; Alabiso, Giulia; Barbasetti di Prun, Allegra; Gentilini, Davide; Busacca, Mauro
Abstract : Aim: The long‐term effects of laparoscopic cystectomy on ovarian reserve in patients with unilateral and bilateral ovarian endometriomas were evaluated. Methods: A total of 22 patients undergoing laparoscopic cystectomy for unilateral endometrioma (n = 10) and bilateral endometriomas (n = 12) were included in the study. Result(s): Serum anti‐Müllerian hormone (AMH) levels significantly decreased from the baseline value (3.98 ± 3.27 ng/mL) one (1.67 ± 1.56 ng/mL), three (2.01 ± 1.70 ng/mL), and six months (2.43 ± 2.39 ng/mL) postoperatively. There was no difference between preoperative and 12 month postoperative AMH levels (4.01 ± 3.39 ng/mL) ( P  > 0.05). Patients with bilateral endometriomas had a significantly higher rate of decline in AMH levels 12 months after surgery than patients with monolateral endometriomas ( P  = 0.035), but in both groups there was no difference in AMH levels at one and 12 months postoperatively ( P  > 0.05). Conclusion(s): AMH levels temporarily decreased after laparoscopic cystectomy for ovarian endometriomas, with complete recovery of preoperative AMH values at 12 months postoperatively. This pattern was equal in patients with bilateral and unilateral ovarian involvement. Patients with bilateral cysts have higher rates of decline of AMH levels compared to patients with unilateral affection.